Postharvest insect pest disinfestation in export Proteaceae cut flowers - the potential of new disinfestation strategies - Ngwenya, Makhosazana Shantelle (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.